Uma releitura do trabalho de Stephen C. Pepper voltada para seu conceito de metáfora - Siqueira, Vinicius Reis de (2019)
This dissertation aims to review Stephen C. Pepper's World Hypotheses (1942) with a new eye, turning to the use of metaphor in that work, and to note its role in the process of knowledge formation. Regarding that, Pepper`s work is akin to developments carried out in the last decades. This dissertation argues, however, that because Pepper develops his thoughts when the indigenous pragmatism of the North American academies starts to lose terrain to logical positivism, and thanks to Pepper's work approximations with the perspective and shape of pragmatist thinking, his work was "eclipsed." The proposal of this work is close to that of a historian, when discussing scientific or philosophical practices contingent on cultural or historical variables that may have influenced the academy and the thought of a given period. In the same vein, it also seeks to offer a broader picture of comparisons and contrasts between traditions of thought in a critical way, but also to produce, or to suggest, new investigations on the Pepperian thought. The research methodology chosen was a bibliographical review seeking to track the development of the conceptions of metaphor in the philosophy of science, since the work of Pepper is focused on a constitution of knowledge in witch its epistemological and metaphysical aspects are molted, as well as the use of sources that offer critical analysis of broader intellectual pathways. From the constructed narrative, it was presented a contemporary way of conceiving the precise cognitive aspect that metaphorical language has on the formation of knowledge, as presented, e.g., by Lakoff and Johnson. Finally, it suggests how Pepper`s thought could be relevant in the discussions about the role of metaphor in the understanding and communication of knowledge, both general and scientific.